2016
DOI: 10.1371/journal.pone.0168619
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for Hospitalized Patients with Systemic Lupus Erythematosus in China: 5-Year Update of the Jiangsu Cohort

Abstract: ObjectiveTo identify early signs associated with poor prognosis in Chinese patients with systemic lupus erythematosus (SLE) through a large population-based follow-up study.MethodsMedical records of > 2,500 SLE patients that first hospitalized between 1999–2009 were collected from 26 centers across Jiangsu province, China, and entered into a database. These patients were followed-up for 5 to 15 years, and those remained contact and had known survival status in 2015 were assessed for the association of factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…16 Feng et al in their study also reported that proteinuria and SLEDAI score were not a predictor of mortality, on the contrary it was said that seizure, as one of the manifestation of neuropsychiatry, was an independent predictor. 17 This is slightly different from our study, where the seizure are not a predictor of mortality.…”
Section: Discussioncontrasting
confidence: 89%
“…16 Feng et al in their study also reported that proteinuria and SLEDAI score were not a predictor of mortality, on the contrary it was said that seizure, as one of the manifestation of neuropsychiatry, was an independent predictor. 17 This is slightly different from our study, where the seizure are not a predictor of mortality.…”
Section: Discussioncontrasting
confidence: 89%
“…In China, its prevalence was 97.5 to 100/100,000 [25]. The peak SLE incidence occurs at age 20–29 years, followed by 30–39 years old for females, but in 70–74 years old for males [3], and the female-to-male ratio was about 10:1 in China [68]. The most common symptom of SLE is fatigue, with about 51%~ 90% of SLE patients experiencing fatigue problem [9].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of patients with newly diagnosed LN was signi cantly better in recent years [2]. Especially early diagnosis and treatment of LN can greatly improve the prognosis of patients with SLE [3]. However, there is a lack of high sensitivity and coincidence markers for early diagnosis of LN.…”
Section: Introductionmentioning
confidence: 99%